Pemanfaatan Media Bergambar Pada Pembelajaran Subtema Hewan Disekitarku Terhadap Proses Pembelajaran Siswa Autis Di SDIT Insan Mulia Merangin - Sri Sunarsih (Jurnal Pendidikan Islam, 2021)
This research aims to explore the utilization of pictorial media in animal subtheme learning to the learning process of autistic students at SDIT Insan MuliaMerangin including the utilization of pictorial media in the language skills of autistic students and using animal images to count using qualitative research methods. The data collection techniques in this study are observations using observation instruments set by researchers, interviews of principals and parents of autistic students and documentation including previous studies, student data and other supporting documents. The data collected is analysed by using techniques in qualitative research. The results showed that pictorial media is able to improve the language skills of autistic students and the ability to count.